(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2020)
Drawing on Erin Manning’s concept of the ‘minor gesture’, this article engages with the choreographic and filmic value of gestural hands. It considers Bausch’s choreography as a gestural practice that intervenes into everyday comportment and habits to show or incite potential variation; and it traces how Akerman’s filmic intervention into Bausch’s work intensifies and alters (our readings of) this work in turn, enhancing what is there and adding new orientations to thematic pathways that it might indicate. Akerman’s 1983 documentary Un jour Pina a demandé… includes many activities that involve hands, both on and off stage, as they are engaged in forming dance gestures, but also in smoking, putting on make-up, tying ties, performing gestures of tenderness or of sign language, and also of ‘marking’ movement sequences. Hand gestures, here, embrace both signification and functionality; yet even more importantly, Akerman’s filming brings to the fore their tactile and social dimensions. This is less a matter of appropriating, but of sharing a choreographic concern for gestural hands, testifying to an aesthetic preoccupation with conduct that ultimately belongs to the commitment of Akerman and Bausch to what might be called an ethics of gesture, carried out across the media of dance and film.